Menakar Perlindungan Justice Colaborator - Hariman Satria (Jurnal Konstitusi, 2016)
Corruption is one form of systematic organized crimes performed with complicated modus operandi. Disclosing of this crime, in addition to requiring special equipment, also needs a certain method. One of the methods is using actors who collaborate or justice collaborator. The provisions on justice collaboratororiginally referred to Article 10 paragraph (2) of Law No. 13 of 2006 on Protection of Witnesses and Victims –but there are indications that these provisions do not provide protection to the justice collaborator. Because even though he plays as a collaborating actor,   it does not result in a loss of authority of the state to prosecute the concerned. This provision is considered violating the principle of lex certain criminal law, for  its ambiguity and multiple interpretations. Constitutional Court in its decision No. 42/PUU-VIII/2010states that Article 10 paragraph (2) regarding a quoprovision is not contrary to the 1945 Constitution. Without realizing it, Constitutional Court has come affirming the lack of protection on the collaborating actors. The fate of justice collaboratorthen finds the clarity in Article 10 paragraph (1) of Law No. 31 of 2014 on Protection on Witnesses and Victims. In the future, with reference to a quo provision, there is no guarantee to the justice collaboratorthat he would not be prosecuted either criminal or civil, except for statements or testimony that is not done in good faith. Besides regulated under legislation of Witnesses and Victims Protection, protection of the justice collaboratorhas also been set in UNTOC 2000 and UNCAC 2003.